Guillain‐Barré syndrome: A comprehensive review - Bellanti, R; Rinaldi, S (Wiley Open Access, 2024)
Guillain‐Barré syndrome (GBS) is a potentially devastating yet treatable disorder. A classically postinfectious, immune‐mediated, monophasic polyradiculoneuropathy, it is the leading global cause of acquired neuromuscular paralysis. In most cases, the immunopathological process driving nerve injury is ill‐defined. Diagnosis of GBS relies on clinical features, supported by laboratory findings and electrophysiology. Although previously divided into primary demyelinating or axonal variants, this dichotomy is increasingly challenged, and is not endorsed by the recent European Academy of Neurology (EAN)/Peripheral Nerve Society (PNS) guidelines. Intravenous immunoglobulin and plasma exchange remain the primary modalities of treatment, regardless of the electrophysiological subtype. Most patients recover, but approximately one‐third require mechanical ventilation, and 5% die. Disease activity and treatment response are currently monitored through interval neurological examination and outcome measures, and the potential role of fluid biomarkers is under ongoing scrutiny. Novel potential therapies for GBS are being explored but none have yet modified clinical practice. This review provides a comprehensive update on the pathological and clinical aspects of GBS for clinicians and scientists.